Surveillance of Avian Influenza type A virus in backyard ducks of the provinces of Huaral and Huaura (Lima, Peru) - Valladares G., Jenny (2018)
The aim of this study was to evaluate the presence of avian influenza (AI) virus in backyard domestic ducks in the provinces of Huaral and Huaura (Lima, Peru). Six-hundred cloacal swab specimens were collected and analyzed by virus isolation in chick embryo eggs free from specific pathogens (SPF). The presence of the AI virus was determined by the hemagglutinating activity of the allantoic fluid and confirmed by a commercial kit using monoclonal antibodies. All samples analyzed were negative to the AI virus. The risk of the disease was evaluated using the Monte Carlo simulation (@risk program) which determined that the AI virus would show a maximum stochastic prevalence of 0.33% with a 95% confidence interval in the event of the disease. It was concluded that the birds included in the present study were not infected with the AI virus.